Electroporation and cell killing by milli- to nanosecond pulses and avoiding neuromuscular stimulation in cancer ablation - Emily Gudvangen; Vitalii Kim; Vitalij Novickij; Federico Battista; Andrei G. Pakhomov (Scientific Reports, 2022)
Abstract Ablation therapies aim at eradication of tumors with minimal impact on surrounding healthy tissues. Conventional pulsed electric field (PEF) treatments cause pain and muscle contractions far beyond the ablation area. The ongoing quest is to identify PEF parameters efficient at ablation but not at stimulation. We measured electroporation and cell killing thresholds for 150 ns–1 ms PEF, uni- and bipolar, delivered in 10- to 300-pulse trains at up to 1 MHz rates. Monolayers of murine colon carcinoma cells exposed to PEF were stained with YO-PRO-1 dye to detect electroporation. In 2–4 h, dead cells were labeled with propidium. Electroporation and cell death thresholds determined by matching the stained areas to the electric field intensity were compared to nerve excitation thresholds (Kim et al. in Int J Mol Sci 22(13):7051, 2021). The minimum fourfold ratio of cell killing and stimulation thresholds was achieved with bipolar nanosecond PEF (nsPEF), a sheer benefit over a 500-fold ratio for conventional 100-µs PEF. Increasing the bipolar nsPEF frequency up to 100 kHz within 10-pulse bursts increased ablation thresholds by < 20%. Restricting such bursts to the refractory period after nerve excitation will minimize the number of neuromuscular reactions while maintaining the ablation efficiency and avoiding heating.